2012
DOI: 10.1143/jpsj.81.124502
|View full text |Cite
|
Sign up to set email alerts
|

BosonictJModel in a Stacked Triangular Lattice and Its Phase Diagram

Abstract: In this paper, we study phase diagram of a system of two-component hard-core bosons with nearest-neighbor (NN) pseudo-spin antiferromagnetic (AF) interactions in a stacked triangular lattice. Hamiltonian of the system contains three parameters one of which is the hopping amplitude t between NN sites, and the other two are the NN pseudo-spin exchange interaction J and the one that measures anisotropy of pseudo-spin interactions. Physical states of the system are restricted to the ones without the doubly-occupie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The previous numerical study of the B-t-J model 9,10,16 showed that there appear various phases including superfluid (SF) with Bose-Einstein condensation (BEC), state with the pseudo-spin long-range order, etc. For the most of the parameter regions, the QMC show that the density fluctuation of particles at each lattice site is stable even in the spatially inhomogeneous states like a phaseseparated state.…”
Section: Bosonic T-j Model With Ddi and Derivation Of Effective Mmentioning
confidence: 99%
“…The previous numerical study of the B-t-J model 9,10,16 showed that there appear various phases including superfluid (SF) with Bose-Einstein condensation (BEC), state with the pseudo-spin long-range order, etc. For the most of the parameter regions, the QMC show that the density fluctuation of particles at each lattice site is stable even in the spatially inhomogeneous states like a phaseseparated state.…”
Section: Bosonic T-j Model With Ddi and Derivation Of Effective Mmentioning
confidence: 99%
“…|phys is the physical state of the slave-particle Hilbert space. The previous numerical study of the B-t-J model 10,11,14 show that there appear various phases including superfluid with Bose condensation, state with the pseudo-spin long-range order, etc. For the most of them, the MC simulations show that density fluctuation at each lattice site is not large even in the spatially inhomogeneous states like a phase-separated state.…”
Section: Bosonic T-j Model and Derivation Of Effective Modelmentioning
confidence: 99%
“…Various phases can form in the system (2.1) at T = 0, e.g., states with long-range spin orders (FM, AF, spiral, etc), superfluid with Bose condensation of a and/or b atoms, and superposition of them (the supersolid (SS)) 7,8,14,16 . In the following sections, we shall consider several specific cases of the extended B-t-J model H tJ + H V and derive effective field-theory model.…”
Section: Bosonic T-j Model and Derivation Of Effective Modelmentioning
confidence: 99%
“…Together with the behavior of ρ CSF (not shown), it can be established that the system is in the CSS state for t B /V < 0. 19(1) and the SS state for t B /V > 0. 19(1).…”
Section: U/ V = 1 and μ/ V = 7/2mentioning
confidence: 99%
“…[2] and [3]). Recently, more and more attention has been paid to two-species bosons, where novel quantum phases can emerge due to interspecies and intraspecies interactions [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], which can be tuned experimentally by Feshbach resonances [21,22].…”
Section: Introductionmentioning
confidence: 99%